2015
DOI: 10.1038/hr.2015.77
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of glucocorticoid receptors with RU486 attenuates cardiac damage and adipose tissue inflammation in a rat model of metabolic syndrome

Abstract: Glucocorticoids are stress hormones that modulate metabolic, inflammatory and cardiovascular processes. We recently characterized DahlS.Z-Lepr(fa)/Lepr(fa) (DS/obese) rats, derived from a cross between Dahl salt-sensitive (DS) and Zucker rats, as a new animal model of metabolic syndrome (MetS). We have now investigated the effects of glucocorticoid receptor (GR) blockade on cardiac and adipose tissue pathology and gene expression, as well as on glucose metabolism in this model. DS/obese rats were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…DS/ obese rats die after 15 week of age and their survival rate at 18 weeks was approximately 35% (Hattori et al 2011). From 9 to 13 week, DS/obese rats present progressive hypertension, LV diastolic dysfunction, LV hypertrophy, fibrosis, and insulin resistance Takeshita et al 2015). Also, hyperphagia is gradually reduced after 11 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…DS/ obese rats die after 15 week of age and their survival rate at 18 weeks was approximately 35% (Hattori et al 2011). From 9 to 13 week, DS/obese rats present progressive hypertension, LV diastolic dysfunction, LV hypertrophy, fibrosis, and insulin resistance Takeshita et al 2015). Also, hyperphagia is gradually reduced after 11 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that GR-knockout monocyte-derived macrophages increase pro-inflammatory chemokine CCL5 and decreases interleukin 1α (IL-1α), a cytokine that plays a central role in delaying myofibroblast differentiation during the inflammatory phase of healing after ischemic myocardial injury (Galuppo et al 2017). Blockade of GR inhibited macrophage infiltration and gene expression of monocyte chemoattractant protein-1, osteopontin, cyclooxygenase-2 and tumor necrosis factor-α (TNFα) in the left ventricular myocardium, contributing to attenuation of cardiac injury in rats with metabolic syndrome (Takeshita et al 2015). It is known that IL-10 is a crucial GR target gene in macrophages.…”
Section: Immune Cellsmentioning
confidence: 99%
“…For insulin tolerance tests (ITTs), mice fasted for 5 h were injected intraperitoneally with 1 IU/kg insulin (Actrapid Penfill; Novo Nordisk, Paris, France). Whole-tail vein blood was collected at baseline (t 0 ) and 15 min (t 15 ), and centrifuged plasma samples were stored at 280°C. For both tests, blood glucose was measured at the tail vein using an automatic Accu-Chek Performa glucometer (Roche, Meylan, France) at indicated times.…”
Section: Metabolic Parameter Exploration and In Vivo Insulin Stimulationmentioning
confidence: 99%
“…Furthermore, in vivo MR pharmacological blockade by eplerenone reduces the expression of proinflammatory factors in genetically obese and diabetic mice, suggesting a role for MR as a key factor mediating obesity-related inflammation and insulin resistance (14). The implication of GR in the pathophysiology of metabolic syndrome has been suggested by the pharmacological blockade of GR (by RU486), which improved fasting hyperinsulinemia, insulin resistance, and glucose intolerance (15). More recently, the role of the adipocyte GR was investigated in vivo using constitutive murine models of adipocyte GR deletion (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%